Evaluasi Beton Bertulang terhadap Perlakuan Panas (Tinjauan pada Tegangan Tarik dan Modulus Elastis Tulangan Baja Lateral) - Riswanto, Riswanto; Pujianto, Asat; Zulfiar, Muhammad Heri (Semesta Teknika, 2013)
Fires phenomena have made demands to a building planner to protect, evaluate, and predict the performance of a building after a fires process. The main attention was given to the type of material, in this case, the reinforced concrete that used as a structural element, which due to heating and cooling cycles are alternating, and then the elements of reinforced concrete structures undergo a phase change both in the physical and chemical. This research related to the evaluation of reinforced concrete quality with a focus on heat treatment and reviews tensile stress and elastic modulus of the steel reinforcement. Specimens used in this study was a model of the reinforced concrete beam with a concrete cover types K250 and K300, 7.5 mm of rebar diameter and 2 cm of concrete cover thickness. Heat testing performed after 28 days of treatment with closed combustion in the furnace (heat chamber) without loading at a temperature of 1000ÂºC for 10 hours, holding time for 1 hour, and slows cooling for 10 hours. In normal specimens, the tensile test results show an equivalent stress value of 324.12 MPa. In specimens heat treatment with a concrete cover of K250, the tensile stress value was 259.52 MPa, while in the K300 was 263.76 MPa. Optimum tensile stress value in normal specimens was 568.62 MPa, and in specimens with heat treatment and with the K250 concrete cover was 473.74 MPa and amounted to 494.41 MPa for K300. The value of tensile fracture stress in normal specimens amounted to 552.52 MPa, and in specimens with heat treatment and with the K250 concrete cover amounted to 461.52 MPa and amounted to 465.24 MPa for K300. Elastic modulus values for normal specimen was 1,612,963.61 kg/cm2, while in specimen heat treatment with the K250 concrete cover was 1,287,888.05 kg/cm2 and was 1,311,545.42 kg/cm2 for K300.